2019
DOI: 10.1590/s1678-3921.pab2019.v54.00445
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical attributes and functional properties of flowers of Brazilian feijoa genotypes

Abstract: The objective of this work was to characterize entire flowers of the feijoa (Acca sellowiana) genotypes 'Alcântara', 'Helena', 'Mattos', 'Nonante', and the accession 2316 for dry matter, total antioxidant activity (TAA), and the contents of soluble solids, ascorbic acid, total anthocyanins, total flavonoids, and total phenolic compounds (TPC), as well as for the petal surface areas and colors. The TAA was quantified by the ABTS and DPPH methods. Flowers of the accession 2316 and of the cultivars Alcântara and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 9 publications
1
13
1
1
Order By: Relevance
“…Vitamin C content was determined by the spectrophotometric method, using 2.4-dinitrophenylhydrazine (2.4-DNPH) (Amarante et al, 2019). We used 1 g of the sample macerated in 50 mL of oxalic acid (0.5%).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vitamin C content was determined by the spectrophotometric method, using 2.4-dinitrophenylhydrazine (2.4-DNPH) (Amarante et al, 2019). We used 1 g of the sample macerated in 50 mL of oxalic acid (0.5%).…”
Section: Methodsmentioning
confidence: 99%
“…The flowers were ground and homogenized with an extracting solution (ethanol 95%: HCl 1.5 N -85:15, v/v) and stored for 12 hours at 4°C to determine the total anthocyanin and flavonoid contents. The samples were filtered with a paper filter, and absorbance was measured in a spectrophotometer at the electromagnetic wavelength (λ) of 535 nm for anthocyanins and 374 nm for flavonoids (Amarante et al, 2019). The results were expressed as mg per 100 g -1 of fresh matter, calculated by Equation 1:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For humans, the flower petals are edible and contain, according to the variety, high concentrations of anthocyanins, flavonoids, total phenols, increased antioxidant activity and high soluble solids content (Amarante et al, 2019). Magri et al (2020) found that the petals attain the highest peak of polyphenols, anthocyanins and ascorbic acid in the F2 state, when the petals continue to open and the anthers and filaments have a dark red color, according to the BBCH scale (Ramírez & Kallarackal, 2018b).…”
Section: Introductionmentioning
confidence: 99%